ECONOMIC CONSEQUENCES OF BUSINESS INVESTMENTS IN GREEN TECHNOLOGIES: SUSTAINABILITY AND PROFITABILITY (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2025)
One of the key areas of technological development all over the world is the development of renowned as green technologies which allow to ensure the required level of economic growth without creating additional environmental risks. Recently, in general, green investment or in particular, green bonds have become an effective tool for financing green projects. The objective of the study was to determine the effect of the development of green technologies on energy security and sustainable development of energy technologies. To achieve this goal, the following tasks were solved: the essence and main directions of development of investments in green technologies in the modern investment space were determined; the volume of investments in green technologies in the world was estimated; possible directions of influence of investments in eco-friendly technologies on energy security were outlined.